Drosophila suzukii in Argentina: State of the Art and Further Perspectives - Buonocore Biancheri, María Josefina (2023)
Drosophila suzukii (Matsumura) (Diptera: Drosophilidae), commonly known as spotted-wing drosophila or SWD, is an invasive, severe, and damaging pest, which is able to inflict huge economic losses on soft thin-skinned fruits worldwide. Argentina was not excluded from the rapid invasion of this new and aggressive pest. Berries and cherries are among the most economically important fruits, showing an increasing demand from both domestic and export markets, which make necessary the application of effective and early protection measures. Although SWD is currently established almost everywhere in Argentina, the scarcity of research on and rapid regulatory actions against this pest have probably contributed to its fast spread throughout the country. In view of that, the article reviews first the current threat status of SWD in Argentina, provides summarized information on crop and non-crop host fruits, seasonal variation and population dynamics, resident natural enemy assemblages, and describes control actions implemented to date. Finally, the need to focus local control actions within an integrated national SWD management program is emphasized. The development and application of complementary eco-friendly strategies, such as Sterile Insect Technique, biological control, mass trapping, and the use of innovative lactone-derived synthetic insecticides with extremely low toxicity for SWD parasitoids, in environmentally distinguishable Argentinian regions is also highlighted.